Research and Realization of the Web-based OA, MIS and DSS System Integration for Miniature Companies - Mei Fen, Lin (2003)
The establishment of integrated information system for miniature companies to involve in e-business is a project worth studying. It is significant to millions of miniature companies. According to current situation of miniature companies, this paper brings forward a research on the Web-based information system integration in miniature companies, which can be an entrance for miniature companies to merge in the tide of E-business. This paper discusses the feasibility, appropriate mechanisms and key technology for integrating OA, MIS and DSS into a single MIS in the Browser/Server (B/S) based architecture for miniature companies. Nowadays, information system includes OA, MIS and DSS that responsible for special business level. Besides that, the development of information system is mainly based on three models: Mainframe-Terminal (M-T) model upon stand-alone computer, Client/Server (C/S) model upon Intranet and Browser/Server (B/S) model upon Internet. The paper is attempted to present the possibility of using advanced technologies, such as ASP (Active Server Pages) and SQL Server, etc. for the Web-based integration of OA, MIS and DSS into a single MIS in the B/S based architecture. The integrated system will enhance communication between different types of data and realize OA, MIS and DSS functions, such as data processing, query processing, statistics and analysis. Thus the system will realize the functional integration and information integration in some degree according to the requirement of miniature companies. Besides that, the integrated system will consist of the business component as an entrance for miniature company to step in e-business. A case study is also bringing forward to show an approach of realizing such kind of Web-based system integration. To sum up, research and realization of the Web-based OA, MIS and DSS system integration will not only improve the working efficiency and effectiveness, but also transform the traditional management model and concept for miniature companies. Such a system will enable miniature companies to improve their competition ability and survival possibility in e-business generation.